The Education Characters Using Local Wisdom Approach - Sari, Dian Cita; Isnaini, Lailatul (Universitas Mercu Buana Yogyakarta, 2021)
Character education in New Normal Era based on a local wisdom approach is a solution to managing education polemic that has been affected by Covid-19 pandemic. One of local wisdom approaches is through G12 (Gurindam Dua Belas) approach which is local wisdom of ethnic Malays as well as didactic literary works. classification of G12 document is used as an effort to strengn character of nation. Various problems of character of nation's children in New Normal era such as moral decadence, sexual disorders, acts of plagiarism, excessive love for social media in younger generation have become a moral crisis that disturbs world of education, family and society, so re is a need for value development. To organize values, Gurindam Dua Belas is a solution that is implemented through habituation and exemplary. This research method is a descriptive method with a qualitative approach, researcher collects primary sources and secondary sources related to discussion, analyzes contents of G12 and results of G12 consist of 12 articles, containing values of Islamic teachings, especially values. purpose of this study is to describe values that exist in Gurindam 12. results obtained include: a) making an effort to introduce and foster local ethnic Malay wisdom, b) to describe character education of Gurindam 12 and values in it, se values include: not lying, prohibition of cursing and criticizing, gentle hands, patient, gentle, sincere, guarding heart, love to give, thrifty, polite, trustworthy, diligent, obedient to mor and far and study hard. c) Growing and fostering values of Gurindam 12 in students. conclusion of this study is that values of G12 need to be actualized continuously by community and young generation in all ir life activities in order to become individuals with Gurindam 12 characteristics.